Os recursos hidroelétricos centro-asiáticos: cooperação versus conflito - Afonso Brardo Duarte, Paulo (Revista Vozes dos Vales: Publicações Acadêmicas, 2014)
This article analyzes some paradigmatic cases of tension between conflict and cooperation, limited cooperation and difficulties in initiating processes of cooperation in Central Asia, particularly in terms of water and electricity, often generating, as we will seek to demonstrate, rivalries that prevent significant advances in regional integration. Instead of participant and non-participant observation techniques, difficult to apply to this object of study, we resorted to semi-structured interviews. We opted for using experts from non-governmental organizations working on the field, as well as the staff of embassies in Central Asian republics, among others. However, some of the respondents in Central Asia have requested anonymity or, in some cases, asked to be cited as local experts. They shall be appointed along the present article as follows: Expert I and Expert II.